The development and validation of the Student Self-feedback Behavior Scale - Yongle Yang; Zi Yan; Jinyu Zhu; Wuyuan Guo; Junsheng Wu; Bingjun Huang (Frontiers in Psychology)
Though the importance and benefits of students’ active role in the feedback process have been widely discussed in the literature, an instrument for measuring students’ self-feedback behavior is still lacking. This paper reports the development and validation of the Self-feedback Behavior Scale (SfBS), which comprises three dimensions (seeking, processing, and using feedback). The SfBS items were constructed in line with the self-feedback behavioral model. One thousand two hundred fifty-two high school students (Grade 10 to Grade 12) in mainland China participated in this survey. The exploratory factor analysis revealed a three-factor model reaffirmed in the confirmatory factor analysis. The multi-group CFA supported the measurement invariance of the SfBS across gender. Using the SfBS can help researchers and teachers better understand students’ self-feedback behavior and optimize benefits derived from the self-feedback process.